2022
DOI: 10.1111/gwmr.12497
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vertical LNAPL Distribution in the Subsurface under the Fluctuating Water Table Effect

Abstract: This column reviews the general features of PHT3D Version 2, a reactive multicomponent transport model that couples the geochemical modeling software PHREEQC-2 (Parkhurst and Appelo 1999) with three-dimensional groundwater flow and transport simulators MODFLOW-2000 and MT3DMS (Zheng and Wang 1999). The original version of PHT3D was developed by Henning Prommer and Version 2 by Henning Prommer and Vincent Post (Prommer and Post 2010). More detailed information about PHT3D is available at the website http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The impact of fluctuations in the water table on solute transport has been investigated by researchers. As mentioned above, Attie et al [13] and Boumaiza et al [14] used modeling to analyze instantaneous changes in the NAPL thickness in water wells caused by water table fluctuations. Guo et al [9] found that water table fluctuations shortened or elongated the transport route of the dissolved phase in the NAPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of fluctuations in the water table on solute transport has been investigated by researchers. As mentioned above, Attie et al [13] and Boumaiza et al [14] used modeling to analyze instantaneous changes in the NAPL thickness in water wells caused by water table fluctuations. Guo et al [9] found that water table fluctuations shortened or elongated the transport route of the dissolved phase in the NAPL.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the convection-diffusion mechanism, it has been found that fluctuations in the water table also have an impact on the solute transport process. For example, Attie et al [13] and Boumaiza et al [14] used modeling to analyze instantaneous changes in the non-aqueous phase liquid (NAPL) thickness in water wells caused by water table fluctuations. Guo et al [9] found that water table fluctuations shortened or elongated the transport route of the dissolved phase in the NAPL.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation, management and remediation of LNAPL-affected sites are challenging due to their complexity (USEPA, 1993;Charbeneau et al, 1995;USEPA, 1996;Tomlinson et al, 2017;Ebrahimi et al, 2019;Boumaiza et al, 2022). Despite these challenges, there are many reports of successes in subsurface LNAPL investigation and detection.…”
Section: Introductionmentioning
confidence: 99%